Food flavors : formation, analysis and packaging influences : proceedings of the 9th International Flavor Conference, the George Charalambous Memorial Symposium, Limnos, Greece, 1-4 July 1997 - International Flavor Conference; Contis, Ellene Tratras (Developments in Food Science (40), 1998)
The 9th International Flavor Conference: George Charalambous Memorial Symposium was held July 1-4, 1997 at the Porto Myrina Palace on the Island of Limnos, Greece. This conference was organized as a tribute to Dr. George Charalambous organizer of the previous eight conferences, who passed away in November of 1994.The symposium brought together a group of international experts in food science and human nutrition to discuss their latest findings in a broad area of food science. Particular emphasis was placed on state-of-the-art instrumentation and methods.The 9th Conference followed the format and traditions of the previous meetings. More than 90 papers/posters were presented by scientists from nineteen countries. Dr. Apostolos Grimanis, a radioanalytical chemist and retired Director of the Radioanalytical Laboratory at the National Center for Scientific Research "Demokritos" in Athens opened the meeting with a tribute to Dr. Charalambous.The Conference Committee announced that the Division of Agricultural and Food Chemistry (American Chemical Society) has agreed to sponsor a Fellowship in Dr. Charalambous' honor in recognition of his tremendous contributions to the Division over many years.